Salmonella enterica serovar Infantis from Food and Human Infections, Switzerland, 2010–2015: Poultry-Related Multidrug Resistant Clones and an Emerging ESBL Producing Clonal Lineage - Hindermann, Denise; Gopinath, Gopal; Chase, Hannah; Negrete, Flavia; Althaus, Denise; Zurfluh, Katrin; Tall, Ben D.; Stephan, Roger; Nüesch-Inderbinen, Magdalena (Frontiers in Microbiology, 2017)
Objectives: The aim of this study was to characterize a collection of 520 Salmonella enterica serovar Infantis strains isolated from food (poultry meat), human infections and environmental sources from the years 2010, 2013 and 2015 in Switzerland. Methods: We performed antimicrobial susceptibility testing and pulsed-field gel electrophoresis (PFGE) analysis on all 520 S. Infantis isolates, and whole genome sequencing (WGS) on 32 selected isolates. Results: The majority (74.8%) of the isolates was multidrug resistant (MDR). PFGE analysis revealed that 270 (51.9%) isolates shared an identity of 90%. All isolates subjected to WGS belonged to sequence type (ST) 32 or a double-locus variant thereof (one isolate). Seven (21.9%) of the sequenced isolates were phylogenetically related to the broiler-associated clone B that emerged in Hungary and subsequently spread within and outside of Europe. In addition, three isolates harboring blaCTX-M-65 on a predicted large (~320 kb) plasmid grouped in a distinct cluster. Conclusions: This study documents the presence of the Hungarian clone B and related clones in food and human isolates between 2010 and 2015, and the emergence of a blaCTX-M-65 harboring MDR S. serovar Infantis lineage.